Compatibility Prediction of Eclipse Third-Party Plug-ins in New Eclipse Releases - Businge, John; Serebrenik, Alexander; van den Brand, Mark (IEEE, 2012)
Incompatibility between applications developed on top of frameworks with new versions of the frameworks is a big nightmare to both developers and users of the applications. Understanding the factors that cause incompatibilities is a step to solving them. One such direction is to analyze and identify parts of the reusable code of the framework that are prone to change. In this study we carried out an empirical investigation on 11 Eclipse SDK releases (1.0 to 3.7) and 288 Eclipse thirdparty plug-ins (ETPs) with two main goals: First, to determine the relationship between the age of Eclipse non-APIs (internal implementations) used by an ETP and the compatibility of the ETP. We found that third-party plug-in that use only old non-APIs have a high chance of compatibility success in new SDK releases compared to those that use at least one newly introduced non-API. Second, our goal was to build and test a predictive model for the compatibility of an ETP, supported in a given SDK release in a newer SDK release. Our findings produced 23 statistically significant prediction models having high values of the strength of the relationship between the predictors and the prediction (logistic regression R2 of up to 0.810). In addition, the results from model testing indicate high values of up to 100% of precision and recall and up to 98% of accuracy of the predictions. Finally, despite the fact that SDK releases with API breaking changes, i.e., 1.0, 2.0 and 3.0, have got nothing to do with non-APIs, our findings reveal that non-APIs introduced in these releases have a significant impact on the compatibility of the ETPs that use them.
Keywords: Eclipse; Plug-ins; Non-APIs; Prediction